2017
DOI: 10.1016/j.molmet.2017.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Rev-Erb co-regulates muscle regeneration via tethered interaction with the NF-Y cistrome

Abstract: ObjectiveThe loss of skeletal muscle mass and strength are a central feature of traumatic injury and degenerative myopathies. Unfortunately, pharmacological interventions typically fail to stem the long-term decline in quality of life. Reduced Rev-Erb-mediated gene suppression in cultured C2C12 myoblasts has been shown to stimulate myoblast differentiation. Yet the mechanisms that allow Rev-Erb to pleiotropically inhibit muscle differentiation are not well understood. In this study, we sought to elucidate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 26 publications
8
31
1
Order By: Relevance
“…In accord with previous studies, we observed that heterozygous REV-ERB mice in addition to possessing heightened regenerative capacity interestingly had a greater total average body mass than wildtype mice [16] (Fig 1A). Firstly, we quantified the expression of Rev-erbα in the SkM of Nr1d1 +/+ , Nr1d1 +/and Nr1d1 -/mice at CT8 and found that Rev-erbα gene expression was dose dependently linked to Nr1d1 genotype as partial loss of Rev-erbα resulted in a reduction in REV-ERBα expression ( Fig 1B).…”
Section: Rev-erb Expression Modulates Body Composition and Muscle Fusupporting
confidence: 92%
See 4 more Smart Citations
“…In accord with previous studies, we observed that heterozygous REV-ERB mice in addition to possessing heightened regenerative capacity interestingly had a greater total average body mass than wildtype mice [16] (Fig 1A). Firstly, we quantified the expression of Rev-erbα in the SkM of Nr1d1 +/+ , Nr1d1 +/and Nr1d1 -/mice at CT8 and found that Rev-erbα gene expression was dose dependently linked to Nr1d1 genotype as partial loss of Rev-erbα resulted in a reduction in REV-ERBα expression ( Fig 1B).…”
Section: Rev-erb Expression Modulates Body Composition and Muscle Fusupporting
confidence: 92%
“…The nuclear receptor REV-ERB is a key repressor of the molecular clock and modulates metabolic and developmental pathways. Our study wished to thoroughly understand how Rev-erb expression levels impacts metabolism and muscle morphology due to a previous observation that Nr1d1 heterozygous mice have superior muscle fiber size [16]. In this study we illustrate that Nr1d1-heterozygosity increased glucose clearance, fatty acid utilization, gluconeogenesis, and also boosted lean mass accumulation without generating higher adiposity in chow-fed mice.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations